2018
DOI: 10.1111/cns.12857
|View full text |Cite
|
Sign up to set email alerts
|

Coping behavior in multiple sclerosis—complementary and alternative medicine: A cross‐sectional study

Abstract: SummaryMain ProblemTreatment options for multiple sclerosis (MS) have enlarged tremendously over the last years. Nonetheless, lots of patients look for alternative treatment options. The use of complementary and alternative medicine (CAM) is widespread in MS, however, its scientific investigation is limited so far. The aim of the study is to analyse clinical and demographical differences of MS patients in dependency of their CAM utilization as coping strategy.MethodsA total of 254 patients with a clinically de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
3
11
1
Order By: Relevance
“…Regarding Correlation among selfmanagement variables of the patients under the study through Pre, Post1 &Post2 phases, showed positive statistically significant correlation regarding all measured variables of self-management. This finding is consistent with (Rommer et al, 2018) in his study about Coping behavior among patients, and clarified that MS causes multiple stressors for patients, in which all required different methods of coping, influenced by the level of impairment, and tackling more intensively with their disease.…”
Section: Regarding Relation Of Total Fatiguesupporting
confidence: 90%
“…Regarding Correlation among selfmanagement variables of the patients under the study through Pre, Post1 &Post2 phases, showed positive statistically significant correlation regarding all measured variables of self-management. This finding is consistent with (Rommer et al, 2018) in his study about Coping behavior among patients, and clarified that MS causes multiple stressors for patients, in which all required different methods of coping, influenced by the level of impairment, and tackling more intensively with their disease.…”
Section: Regarding Relation Of Total Fatiguesupporting
confidence: 90%
“…In regard to the correlation between health maintenance behavior and overall fatigue among MS patients, there was a statistically significant negative correlation with p-value (.007). This finding in consistent with [63] who revealed that MS causes multiple stressors for patients, in which all require different methods of coping, influenced by the level of impairment, and tackling more intensively with their disease, [64] added that adaptive coping strategies in MS is beneficial for psychosocial adjustment and management of disease progression. Furthermore [65] mentioned that demonstrating a desirable individual performance such as (modulation of activities, appropriate environments, having adequate knowledge about the disease, good , seeking for further information about MS) are all expressed that patients can successfully cope with disease through self-management behaviors.…”
Section: Discussionsupporting
confidence: 79%
“…Belladonna is traditionally used for the treatment of several conditions, including cold and hay fever, headache, inflammation, motion sickness, and peptic ulcers, and to prevent bronchial spasms in whooping cough and asthma. Belladonna is also effective in treating rheumatism, sciatica, neuralgia, and psychiatric disorders. , The plant has also been shown to possess significant antioxidant, antimicrobial, analgesic, and anti-inflammatory activities, especially by those fractions that are extracted using methanol . Atropine is extensively used as an antispasmodic agent and an analgesic for gastrointestinal spasms and biliary and hepatic colic.…”
Section: Pharmacotherapeutic Characterization Of Belladonnamentioning
confidence: 99%
“…Belladonna is also effective in treating rheumatism, sciatica, neuralgia, and psychiatric disorders. 94,95 The plant has also been shown to possess significant antioxidant, antimicrobial, analgesic, and anti-inflammatory activities, especially by those fractions that are extracted using methanol. 96 Atropine is extensively used as an antispasmodic agent and an analgesic for gastrointestinal spasms and biliary and hepatic colic.…”
Section: Mechanism Of Action Of Belladonna Alkaloidsmentioning
confidence: 99%